Development of an information measuring and control system for a quadrocopter - V. V. Sleptsov; V. L. Afonin; A. E. Ablaeva; Ba Phuong Dinh (Российский технологический журнал)
The article deals with the issues of synthesis and analysis of information-measuring and control systems of quadrocopters. The main sensors and modules used to determine the parameters of the coordinates of quadrocopters are given. The speed-controlled electric drives used for control and the features of their choice are considered. The coordinate systems (fixed and mobile) and the kinematic scheme are given, according to which a system of differential equations is presented. The system describes the dynamics of the quadrocopter movement and takes into account the expected smooth movement of the quadrocopter with small roll and pitch angles. A functional scheme and a mathematical model of the information-measuring and control system of the quadrocopter in the form of a block diagram are developed taking into account the influence of delays in the receipt of information from the sensors of the quadrocopter parameters. A special feature of this work is to take into account the specific characteristics of the elements: adjustable electric drives (both direct and alternating current), parameter sensors (barometers, accelerometers, rangefinders, etc.). The paper studies an illustrative algorithm for the operation of the informationmeasuring and control system of the quadcopter. The type and parameters of the controllers of the quadrocopter control systems are determined. Special attention is paid to the settings for the control contours at the corresponding coordinates. The influence of the controllers of the coordinate control systems of the information-measuring and control systems of the quadrocopter on the effects of the interaction of coordinates is considered. The simulation results are presented. The optimal number of control loops for the coordinates of the information-measuring and control systems of the quadrocopter and the optimal type of settings for obtaining smooth transients (without overshoot) and for excluding the interaction of coordinates on quality indicators are determined.